Opportunities And Challenges Of The Halal Industry In The Field Of Household Goods - Yulistya Rahma Fitri; Wafiqoh Nur Azizah Itsnatani; Haliza Alfin; Diyah Shafa Abinita; Maulana Alivio Biyan Soffat; Muhammad Ghoris Mighwar; Reza Akmal Kafi (GERASI INSAN NUSANTARA, 2026)
This research aims to describe the opportunities and challenges of the halal industry in the household goods sector in Indonesia. The approach used is descriptive qualitative by analyzing secondary data from various literature, industry reports, and government regulations. The results of the study show that increasing public awareness of halal products encourages economic growth in the household sector and opens up large export opportunities. However, lack of consumer understanding, supply chain transparency, and limited halal certification are the main obstacles. Therefore, synergy between the government, producers, and consumers is needed to strengthen the household halal industry ecosystem